Effects of low-volume court-based sprint interval training on aerobic capacity and sport-specific endurance performance in competitive tennis players - Yang, W.; Yin, L.; Poon, E.T.-C.; Ho, I.M.K.; Liu, H.; Qi, B.; Li, Q.; Li, Y. (Biology of Sport, 2025)
Sprint interval training (SIT) is a potent exercise strategy to enhance athletes` aerobic capacity in a time-efficient manner. The purpose of this study was to examine the effect of a low volume court-based SIT program on aerobiccapacity and sport-specific endurance performance forcompetitive tennis players. Sixteen competitive collegiate tennis players were randomly assigned to the SIT (court-based repeated-sprint training) and traditional endurance training (ET; 45-min continuous treadmill running) groups for a 6-week intervention (3 sessions/week). The maximal oxygen uptake (VO2max), minute ventilation at peak exercise (VEmax), ventilatory anaerobicthreshold in percentage of VO2max (VT/VO2), and elimination rate of blood lactate (BLAer) were assessed, whereas the Yo-Yo Intermittent Recovery Test Level 2 (YoYo-IR2) and the tennis-specific HIT&TURN test were conducted at baseline and after the intervention. Both SIT and ET showed significant improvements in VO2max (p < 0.01) with moderate effect sizes (ES = 0.64 and 0.98, respectively), as well as in VEmax (p < 0.01) with small effect sizes (ES = 0.23 and 0.21, respectively), and VT/VO2 (p < 0.01) with large effect sizes (ES = 2.37 and 3.85, respectively). The BLAer improved significantly in SIT (ES = 1.03; p < 0.05) whereas no significant changes occurred in ET. The magnitude-based decision showed a clear and superior improvement in both YoYo-IR2 (ES = 0.69) and HIT&TURN (ES = 1.72) tests in SIT than ET. Compared with traditional ET, court based SIT can be a time-efficient strategy to improve aerobic capacity and tennis-specific endurance without requiring specialized equipment for competitive tennis players.